Effects of sublethal exposure of diuron on adults of Javanese medaka (Oryzias javanicus, Bleeker 1854) using histopathology and immunochemistry techniques - Kamarudin, Nur Amiera (2019)
Diuron has been used around the world either as herbicide or bioactive ingredient in the antifouling paint. However, the knowledge on the impacts of Diuron toxicity that could adversely affect the non-targeted aquatic organisms especially fish is still lacking. Therefore, this study was conducted to observe the toxicity of phenyl-urea herbicide Diuron on adult Javanese medaka (Oryzias javanicus) and the possible sublethal effects at the cellular level of the selected vital organ of adults’ Javanese medaka which used as a novel model organism. The distinctive characteristic of the Javanese medaka as euryhaline species can be used to represent a wide range of salinity of the contaminated aquatic ecosystems. The methods used to evaluate the effects of Diuron on vital organs through histopathology and immunohistochemistry technique. Histological assessment was conducted by using the haematoxylin and eosin (H and E) staining protocol where the samples were preserved in 10% buffered formalin and section at 5 μm thickness. While, the apoptosis events or cell death can be detected by using Caspase-3 antibody which mediated to the Caspase protein as programmed cell death (apoptosis). Results of acute exposure showed that 100% mortality of Javanese medaka was at 20.0 mg/L of 96-hours of Diuron exposure. The median lethal concentration 50% (LC50-96h) of the acute exposure is 5.9 mg/L. Semi-quantitative analysis from the chronic exposure showed significantly difference (p<0.05) from moderate to severe deformities in the liver and kidney tissues exposed at a higher concentration of sublethal level (500 μg/L and 1000 μg/L) as compared to control treatment while mild lesion alterations were already showed even at lowest concentration of Diuron exposure, 1.0 μg/L. The most evident and observable severity of the lesions in the liver is vacuolation, congestion, and nodule necrosis while, kidney which is the most effected organ showed severity in tubule degeneration, glomerulus shrinkage, and hemosiderin. In addition, Diuron is proven as an endocrine disrupting chemical (EDC) which can interfere with the normal functions of the endocrine system of fish. In addition, Diuron caused the decreasing in gonadal staging and maturity of germ cells in oogenesis and spermatogenesis of female and male Javanese medaka. Therefore, the impairments and destruction in liver and kidney, as well as the modification of gonads in Javanese medaka, can reflect the effect in physiology, life cycle and population in the natural environment. The health of the aquatic ecosystem can also be assessed by using the immunohistochemistry as a biomarker tool. Results showed the significant increment percentages of the apoptotic events as compared to the control of liver, kidney, ovary, and testis; 31.6%, 32.5%, 46.5% and 51.5% respectively at the highest concentration of Diuron exposure (p<0.05). Findings of this study will strengthen the documentation in developing Javanese medaka as a novel model organism for tropical region in particular of aquatic toxicological studies. In summation, histopathology study is good enough to be a good biomarker to assess the health quality of aquatic ecosystem through histology of fish’s vital organs and for further investigation later on, immunohistochemistry analysis have the ability to visualize the distribution and localization of the specific tissues components with specific antigens and antibodies of stress or death fish tissues from the contaminated aquatic ecosystems. Also, although the concentration of Diuron in Malaysia is still unthreatening, this emerging hazardous chemical can seriously affect the aquatic ecosystems and its living organisms in later years.